Student satisfaction in the master's programs of education of the Universidad Nacional Mayor de San Marcos - Romero-Ocas, Silvio (2021)
The research provides knowledge of a relevant indicator to ensure educational quality in the master's programs from the Faculty of Education of the Universidad Nacional Mayor de San Marcos (UNMSM), aiming to establish the level of global student satisfaction and by dimensions, using for its study the quantitative approach, non-experimental design, transversal and descriptive. In the accidental non-probabilistic sample, 217 students participated. The instrument used for data collection was a questionnaire consisting of 38 items with likert rating scale responses, and design was performed considering three dimensions of the matrix of standards of the National System of Evaluation, Accreditation and Certification of Educational Quality (SINEACE). The results found the average level of Global Student Satisfaction with a percentage of 59.8%, and regarding dimensions: strategic management, integral training and institutional support, they also showed an average level satisfaction of 51%, 62% and 50% respectively. It was concluded that the integral training dimension is the one that acquires the highest percentage of satisfaction. Finally, the study carried out contributes scientifically so that the corresponding authorities make timely decisions that contribute to the quality of education and continuous improvement.